A Digital Marketing-Based Public Relations Management Strategy for Increasing the Appeal of State Senior High School 3 Cilacap to Prospective Students - Ambarwati Syafitri; Fatkuroji Fatkuroji; Hamdan Husein Batubara (Universitas Negeri Malang, 2026)
Abstract: This study aims to analyze digital marketing-based public relations management strategies for increasing the appeal of MAN 3 Cilacap to new students, as well as to identify the supporting factors, inhibiting factors, and implications of these strategies for the institution’s image. The study employs a qualitative approach using a case study design to gain an in-depth understanding of the implementation of digital marketing-based public relations strategies in the context of a madrasah. The research informants consisted of the Madrasah Vice Principal for Public Relations and the Madrasah Vice Principal for Student Affairs, who were selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, then analyzed using the Miles, Huberman, and Saldaña interactive model, which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the digital marketing-based public relations management strategy is implemented through four management functions: planning, organizing, executing, and evaluating. Promotional strategies are implemented by leveraging digital media such as Instagram, Facebook, YouTube, WhatsApp, and the madrasah’s official website, and are reinforced through direct outreach, the publicization of student achievements, extracurricular activities, and alumni engagement. Key supporting factors include leadership support, teamwork, availability of digital media, and student achievements, while inhibiting factors include limited human resources, competition among educational institutions, and consistency in content production. The research findings indicate that digital marketing-based public relations strategies contribute to enhancing the visibility, positive image, and appeal of MAN 3 Cilacap within the community. This study strengthens the field of educational public relations management by emphasizing the importance of integrating management functions and digital marketing as an effective communication strategy in the digital age. Keywords: public relations management, digital marketing, educational promotion, institutional image, student appeal.